Schottky Contacts Regularized Linear Regression for Signal Inconsistency Circumvent in Resistive Gas Micro‐Nanosensors. Issue 12 (5th November 2021) - Zhao, Yuxin; Su, Yue; Guo, Mengya; Liu, Liqun; Chen, Peng; Song, Anqi; Yu, Wei; Hu, Shi; Zhao, Rongjian; Fang, Zhen; Zhang, Huacheng; Zhao, Yanli; et al.
Abstract: In the frontier resistive micro‐nano gas sensors, the change rate reliability between the measured quantity and output signals has long been puzzled by the ineluctable device‐to‐device and run‐to‐run disparities. Here, a neotype sensing data interpretation method to circumvent these signal inconsistencies is reported. The method is based on discovery of a strong linear relation between the initial resistance in air ( R a ) and the absolute change in resistance after exposure to target gas ( R a – R g ). Metal oxide gas sensors based on a micro‐hot‐plate are employed as the model system. The study finds that such correlation has a wide universality, even for devices incorporated with different sensing materials or under different gas atmosphere. Furthermore, this rule can also be extensible to graphene‐based interdigital microelectrode. In situ probe scanning analyses illuminate that the linear dependence is closely related to work function matching level between metal electrode and sensitive layer. The Schottky barrier at metal‐semiconductor junctions is the prominent parameter, whose height (ϕB ) can fundamentally impact material/electrode contact resistance, thereby further affecting the realistic nature expression of sensing materials. Using this correlation, a calibration procedure is proposed and embed in a fully integrated pocket‐size sensor prototype, whose response outcomes demonstrated high credibility as compared to commercial apparatus. Abstract : In resistive micro‐nano gas sensors, a strong linear correlation between initial resistance of sensing material in the reference air ( R a ) and absolute change in resistance after target gas interaction ( R a – R g ) has been discovered. This underlying pattern is not only helpful to suppress the device‐to‐device and run‐to‐run variations, but also redefines the way of sensing materials screening for practical use.